2019
DOI: 10.1002/clc.23153
|View full text |Cite
|
Sign up to set email alerts
|

Low serum albumin: A significant predictor of reduced survival in patients with chronic heart failure

Abstract: Background Low serum albumin is common in patients with chronic heart failure (HF). Hypothesis Albumin may have an impact on clinical outcome in HF. We evaluated the effect of albumin levels on clinical outcome in a real‐world cohort of patients with HF. Methods All patients with HF at a health maintenance organization were followed for cardiac‐related hospitalizations and death. Results A total of 5779 HF patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 23 publications
2
40
1
Order By: Relevance
“…In the present study, albumin was commonly determined as the top predictor in both of ML and LR models. Although several recent studies have identified hypoalbuminemia as an independent predictor of mortality in CVD[20] (i.e., HF,[2123] myocardial infarction,[2426] or hemodialysis[2729]), albumin was not included in most of the risk scores for mortality in CVD. [3035] The insufficient recognition of albumin as a risk factor for mortality may be due to the strong interaction with other risk factors (i.e., hemoglobin and body weight) or missing values in previous observational studies due to the low attention to its risk.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, albumin was commonly determined as the top predictor in both of ML and LR models. Although several recent studies have identified hypoalbuminemia as an independent predictor of mortality in CVD[20] (i.e., HF,[2123] myocardial infarction,[2426] or hemodialysis[2729]), albumin was not included in most of the risk scores for mortality in CVD. [3035] The insufficient recognition of albumin as a risk factor for mortality may be due to the strong interaction with other risk factors (i.e., hemoglobin and body weight) or missing values in previous observational studies due to the low attention to its risk.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin and creatinine were both indicators of nutrition status which was related to the development of malnutrition-inflammation-atherosclerosis (MIA) syndrome. Hypoalbuminemia was a relative predictor of ESA responsiveness and survival in hemodialysis patients [ 25 27 ], which was probably also associated with inflammatory reaction. Predialysis serum creatinine level, a potential surrogate of muscle mass, was negatively related to mortality in HD and peritoneal dialysis patients [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Albumin is found in both intra-and extracellular proteins, and its serum concentration is typically within the range of 35–50 g/L in healthy individuals. Furthermore, changes in serum albumin levels are associated with various disorders; for example, albumin concentration increases can be associated with prediabetes development, incident hemodialysis, and administration of certain types of drugs, while a decrease may be observed in patients with acute heart failure, sepsis, and hypoalbuminemia [ 35 , 36 , 37 , 38 , 39 ]. There-fore, we first determined the sensitivity of the CUPRAC assay regarding the glycation re-action that occurred in tubes containing different concentrations of BSA (2–10 mg/mL) and the same amount of glucose (0.1 M) in a phosphate buffer environment (pH = 7.4).…”
Section: Resultsmentioning
confidence: 99%